Repair of isolated atrial septal defect in infants less than 12 months improves symptoms of chronic lung disease or shunt-related pulmonary hypertension. (16th March 2020) - Charisopoulou, Dafni; Bini, Roberta Margarita; Riley, Gillian; Janagarajan, Kalai; Moledina, Shahin; Marek, Jan
Abstract: Introduction: Infants with isolated atrial septal defects are usually minimally symptomatic, and repair is typically performed after infancy. Early repair may be considered if there is high pulmonary blood flow and reduced respiratory reserve or early signs of pulmonary hypertension. Our aim was to review the characteristics and outcomes of a cohort of patients who underwent infant repair at our institute. Methods: The study included 56 infants (28 female, 19 trisomy 21) with isolated atrial septal defect (age: 8 months (1.5–12), weight: 6 kg (2.8–7.5), echo Qp/Qs: 1.9 ± 0.1) who underwent surgical closure (20 fenestrated). Three groups were identified: 1) chronic lung disease and pulmonary hypertension (group A: n = 28%); 2) acutely unwell infants with pulmonary hypertension but no chronic lung disease (group B: n = 20, 36%); and 3) infants with refractory congestive heart failure without either pulmonary hypertension or chronic lung disease (group C: n = 9, 16%). Results: Post-operatively, pulmonary hypertension infants (47/56) showed improvement in tricuspid annular plane systolic excursion z-score (p < 0.001) and right ventricular systolic/diastolic duration ratio (p < 0.05). All ventilator (14.3%) or oxygen-dependent (31.6%) infants could be weaned within 2 weeks after repair. One year later, weight z-score increased in all patients and by +1 in group A, +1.3 in group B and +2 in group C. Over a median follow-up of 1.4 years, three patients died, four patients continued to have pulmonary hypertension evidence and two remained on targeted pulmonary hypertension therapy. Conclusion: Atrial septal defect repair within the first year may improve the clinical status and growth in infants with early signs of pulmonary hypertension or those requiring respiratory support and facilitate respiratory management.